Climate Change Increases the Potential for Extreme Wildfires. Issue 14 (29th July 2019) - Di Virgilio, Giovanni; Evans, Jason P.; Blake, Stephanie A. P.; Armstrong, Matthew; Dowdy, Andrew J.; Sharples, Jason; McRae, Rick
Abstract: Pyrocumulonimbus (pyroCb) wildfires cause devastation in many regions globally. Given that fire‐atmosphere coupling is associated with pyroCbs, future changes in coincident high index values of atmospheric instability and dryness (C‐Haines) and near‐surface fire weather are assessed for southeastern Australia using a regional climate projection ensemble. We show that observed pyroCb events occur predominantly on forested, rugged landscapes during extreme C‐Haines conditions, but over a wide range of surface fire weather conditions. Statistically significant increases in the number of days where both C‐Haines and near‐surface fire weather values are conducive to pyroCb development are projected across southeastern Australia, predominantly for November (spring), and less strongly for December (summer) in 2060‐2079 versus 1990‐2009, with future C‐Haines increases linked to increased 850‐hPa dewpoint depression. The increased future occurrence of conditions conducive to pyroCb development and their extension into spring have implications for mitigating these dangerous wildfires and urbanizing fire‐prone landscapes. Plain Language Summary: Pyrocumulonimbus wildfires (pyroCb) are extreme wildfires. They involve a coupling between the fire and the atmosphere, which drives dangerous fire conditions that result in fatalities and considerable damage. Climate change could amplify the conditions associated with pyroCb development. We use high‐resolution regional climate projection data to assess future changes in the risk of pyroCb occurrence for southeastern Australia. We demonstrate that atmospheric instability and dryness is a better indicator of pyroCb development than surface fire weather conditions, with topographic roughness and vegetation type also playing roles. Coincidences of high index values of atmospheric conditions (tropospheric instability and dryness) and surface fire weather conditions (temperature, humidity, wind speed, and precipitation) associated with pyroCb development are projected to increase in frequency predominantly for November (spring) in 2060‐2079 versus 1990‐2009, but less so for summer. The extension of the season conducive to pyroCbs into spring is important because Australian pyroCbs are typically summer phenomena. A change in seasonality has implications for resource allocations by fire agencies. Projected changes in the conditions conducive to pyroCbs are primarily associated with increased dryness at 1.5‐km altitude. These findings are relevant to the mitigation of pyroCbs, and they have implications for continued urban expansion on fire‐prone landscapes. Key Points: Significant increases in the frequency of conditions conducive to pyrocumulonimbus fires occur in November (Spring) 2060‐2079 versus 1990‐2009 Atmospheric instability and dryness are better indicators of pyrocumulonimbus fire development than surface fire weather Locations in southeast Australia where these changes are projected to occur are identified